2024
DOI: 10.1039/d4ce00021h
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of new cocrystals beyond serendipity: lessons learned from successes and failures

Si Nga Wong,
Minqi Fu,
Si Li
et al.

Abstract: The past decade has witnessed remarkable progress in cocrystal research, by virtue of the desires to address problematic properties of drugs. Notwithstanding the rapid advancements in knowledge-based cocrystal design, such...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 188 publications
0
3
0
Order By: Relevance
“…16 Interestingly, it has been demonstrated that CAF and 4-HBA cocrystallize in a 1:1 molar ratio, resulting in a mixture of (2:1) and (1:2) cocrystals, 12 which contradicts computational predictions that suggest greater stability for the (1:1) cocrystals. 9,16 However, the formation of CAF/4-HBA (1:1) cocrystals has not yet been achieved. Additionally, it has been revealed that the stoichiometry of the resulting cocrystals is influenced by the initial concentration of the components.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Interestingly, it has been demonstrated that CAF and 4-HBA cocrystallize in a 1:1 molar ratio, resulting in a mixture of (2:1) and (1:2) cocrystals, 12 which contradicts computational predictions that suggest greater stability for the (1:1) cocrystals. 9,16 However, the formation of CAF/4-HBA (1:1) cocrystals has not yet been achieved. Additionally, it has been revealed that the stoichiometry of the resulting cocrystals is influenced by the initial concentration of the components.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the screening of cocrystals with diverse stoichiometries has garnered considerable attention due to its inherent advantages. For instance, extensive research on the cocrystallization of caffeine (CAF) with 4-hydroxybenzoic acid (4-HBA) has been conducted using both experimental and computational methods . Interestingly, it has been demonstrated that CAF and 4-HBA cocrystallize in a 1:1 molar ratio, resulting in a mixture of (2:1) and (1:2) cocrystals, which contradicts computational predictions that suggest greater stability for the (1:1) cocrystals. , However, the formation of CAF/4-HBA (1:1) cocrystals has not yet been achieved. Additionally, it has been revealed that the stoichiometry of the resulting cocrystals is influenced by the initial concentration of the components .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation